Investigation of dielectric and electro-optical parameters of high birefringent nematic liquid crystal doped with TiO2 nanoparticles and its applicability toward liquid crystal displays. (22nd September 2019) - Katiyar, Rohit; Pathak, Govind; Agrahari, Kaushlendra; Srivastava, Atul; Garbat, Katarzyna; Manohar, Rajiv
Abstract: In the present study, anatase TiO2 nanoparticles (NPs) have been doped in three different concentrations into nematic liquid crystal (NLC) 2020 (fluorinated 4'-alkylphenyl-4-isothiocyanatotolanes). The response time and contrast ratio has decreased and increased, respectively for the NLC-NPs composite system. Polarizing optical microscope images reveal that alignment has been improved after the doping of TiO2 NPs. Dielectric measurement study shows that the tan δ has been decreased and relaxation frequency shifted toward the lower frequency region for the doped system. The outcome of the present investigation may be very useful in the improvement of electro-optical features of liquid crystal displays.